Reversible Charles Bonnet Syndrome After Oculoplastic Procedures. Issue 3 (September 2018) - Beaulieu, Robert A.; Tamboli, Diana A.; Armstrong, Blair K.; Hogan, R. Nick; Mancini, Ronald
Abstract : Abstract: Individuals with Charles Bonnet syndrome (CBS) typically have severe visual loss and experience visual hallucinations yet have no psychiatric disease. Visual impairment often is due to end-stage glaucoma or macular degeneration. We report 3 cases of CBS in patients who underwent an oculoplastic surgical procedure. One patient experienced binocular visual distortion due to excessive topical ophthalmic ointment, and 2 patients experienced monocular visual impairment from patching. Visual hallucinations resolved once vision returned to baseline. We highlight the possibility of transient CBS in postoperative patients who have temporary iatrogenic vision impairment in one or both eyes.